1991
DOI: 10.1046/j.1468-2982.1991.1106269.x
|View full text |Cite
|
Sign up to set email alerts
|

The Insulin Tolerance Test and the Ovine Corticotrophin-Releasing Hormone Test in Episodic Cluster Headache

Abstract: Clinical observations indicate a central nervous system, probably hypothalamic, involvement in cluster headache pathogenesis. In order to investigate the supposed hypothalamic involvement in cluster headache, we followed the hypothalamic-pituitary-adrenal axis and autonomic responses to the insulin tolerance test and the ovine corticotrophin-releasing hormone test in episodic cluster headache patients, both during remission and during the cluster period. The study revealed increased basal cortisol levels in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 20 publications
1
22
0
1
Order By: Relevance
“…Interleukin-1 alpha plasma levels are normal (16) in CH and cortisol levels are elevated (17)(18)(19) so that low mononuclear beta-endorphin levels are unlikely to be explained on this basis.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-1 alpha plasma levels are normal (16) in CH and cortisol levels are elevated (17)(18)(19) so that low mononuclear beta-endorphin levels are unlikely to be explained on this basis.…”
Section: Discussionmentioning
confidence: 99%
“…Chazot et al [31] found that the normal morning peak in plasma cortisol was significantly phaseadvanced in patients with CH, although this finding has not been replicated by other investigators [32][33][34][35][36]. Multiple investigators have found that CH patients typically have elevations in baseline plasma cortisol levels [32][33][34][35][36], particularly during cluster periods, and that these elevations are independent of the presence of pain because they are not seen in patients with chronic low back pain [37]. Further elevations in plasma cortisol levels have been associated with specific CH attacks [34].…”
Section: Pathophysiologic Rationale For the Therapeutic Efficacy Of Cmentioning
confidence: 98%
“…Further elevations in plasma cortisol levels have been associated with specific CH attacks [34]. Dexamethasone suppression testing in CH patients has been found to be normal [38][39][40]; however, ovine corticotrophin-releasing hormone testing and insulin tolerance testing produced blunted plasma ACTH and cortisol elevations in patients with CH compared with control subjects [37,41]. Leone et al [37,41] have interpreted these collective findings as indicative of a primary dysfunction in the hypothalamic-pituitary-adrenal axis in CH.…”
Section: Pathophysiologic Rationale For the Therapeutic Efficacy Of Cmentioning
confidence: 99%
“…Hypoglycemia also provokes release of the hypothalamic stimulators of ACTH secretion, corticotrophin-releasing hormone (CRH) and vasopressin, into the pituitary portal blood (15) and enhances their turnover in the median eminence (16). Based on this knowledge, insulin-induced hypo-glycemia together with the ovine-CRH (o-CRH) test was studied in cluster headache patients (17). There was a reduced response of the hypothalamic-pituitary-adrenal axis to both in the cluster period and during remission (17).…”
mentioning
confidence: 99%
“…Based on this knowledge, insulin-induced hypo-glycemia together with the ovine-CRH (o-CRH) test was studied in cluster headache patients (17). There was a reduced response of the hypothalamic-pituitary-adrenal axis to both in the cluster period and during remission (17). The question arose if this was secondary to pain or stress rather than indicating a primary hypothalamic dysfunction.…”
mentioning
confidence: 99%